(untitled) (Journal of Tourism & Adventure, 2024)
This study focuses on two major areas of transformative learning and transformative tourism. The study aims to understand how transformative learning theory developed by Jack Mezirow was first introduced to the academia and then adopted in the field of tourism. Transformative travel and tourism is an emerging paradigm in the travel industry, characterized by travel experiences that lead to profound personal growth, self-discovery, and societal benefits. This paper explores the intersections of transformative learning theory and transformational tourism experiences through a qualitative research approach. By synthesizing secondary data from diverse contexts and empirical studies, the study examines how transformative learning processes manifest in the context of travel and tourism. The theoretical framework draws on Mezirow’s transformative learning theory, emphasizing critical reflection and perspective learning. This study is based on a general review through thematic analysis of narratives. The research identifies mechanisms that facilitate transformative experiences during travel. The literatures highlight on novelty seeking, escapism, freedom, self-efficacy, the transformation of consciousness, self-development and personal growth, and subjective wellbeing which is an outcome of transformative travel. This study explores the concepts of transformation, transformative learning, transformational tourism, tourism motivation, tourism destination image, marketing, authenticity, satisfaction, and transformative experiences.